Immuno-Golgi as a tool for analyzing neuronal 3D-dendritic structure in phenotypically characterized neurons - Pinto, Luísa (2012)
Characterization of neuronal dendritic structure in combination with the determination of specific neuronal phenotype or temporal generation is a challenging task. Here we present a novel method that combines bromodioxyuridine (BrdU) immunohistochemistry with Golgi-impregnation technique; with this simple noninvasive method, we are able to determine the tridimensional structure of dendritic arborization and spine shape of neurons born at a specific time in the hippocampus of adult animals. This analysis is relevant in physiological and pathological conditions in which altered neurogenesis is implicated, such as aging or emotional disorders